Learning experience with transapical aortic valve implantation – the initial series from Leipzig - Kempfert, Jörg; Walther, Thomas (Cardiovascular Diagnosis and Therapy, 2012)
Since the first successful transcatheter aortic valve implantation (TAVI) back in 2002 (1), the field of TAVI has seen a rapid development. Soon, two main options in regard to the access for valve delivery evolved. With the transfemoral route (TF) the common femoral artery is entered after surgical dissection or percutaneously using an endovascular closure device.